Turán numbers of theta graphs. (13th July 2020) - Bukh, Boris; Tait, Michael
Abstract: The theta graph Θ _, t consists of two vertices joined by t vertex-disjoint paths, each of length . For fixed odd and large t, we show that the largest graph not containing Θ _, t has at most c_t^1 - 1/n^1 + 1/ edges and that this is tight apart from the value of c_ .